Digital Redlining: Poor Rural Communities' Access to Fintech and Implications for Financial Inclusion. Issue 5 (18th September 2020) - Friedline, Terri; Naraharisetti, Sruthi; Weaver, Addie
ABSTRACT: Financial technologies (fintech) are proposed to expand access to financial services in rural communities as bank branches decline; however, poor rural communities and rural communities of color have limited access to high-speed internet connections required for fintech. Leveraging the universe of U.S. rural zip codes, this paper investigates associations between communities' poverty rates, racial makeup, and rates of fintech. Poor rural communities of color experience digital redlining by having the lowest fintech rates. Rural communities' increasing white population is associated with higher high-speed internet rates, an advantage of whiteness observable even in the presence of high poverty. Implications are discussed.